Pengembangan Aplikasi Medication Reminder Kontrol Berbasis Android Bagi Keluarga Untuk Program Pengobatan Pasien Kusta - Dahoklory, Dorsina Fransisca; Haryanto, Joni; Indarwati, Retno (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Cystitis is a chronic infectious disease caused by Mycobacterium leprae that, if left untreated, causes lasting impairment, worsens the patient's psychological health, and even reduces productivity. The importance of health and the willingness to adhere to a treatment plan are heavily influenced by the family, who are the patient's closest relatives. Smartphones are a communication and information source that are readily available to society in the age of digitization because of its effectiveness in terms of time, energy, and cost. Proof is still required for the development of this application. An exploratory design and two-stage RD methodologies are used in the study. The examination of patient compliance with therapy and the support of their families during the first stage of application prototype. Evaluation using purposive sampling techniques in 20 patients. The second stage of socialization and application eligibility testing in 10 patients Data collection using questionnaire. Data analysis is done descriptively and analytically. The results of the study showed relatively good family support (50%) and low patient medication adherence (80%). At the development stage, the app produces menus for patients and families: education, checking records, calendars, and consultations. The test results of the application have received good acceptance from users. The development of the medication reminder application can be used as a medium to help the cyst patient and their family complete the treatment program received by the patient.